Perempuan dalam Sastra Lisan Pulau Raas: Kajian Gender - Ahmadi, Anas (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Studies on the relationship between women and oral literature have been interesting topics to discuss. This paper, therefore, describes Raas Island Oral Literature (RIOL) or Sastra Lisan di Pulau Raas (SLPR) by focusing on women from a gender perspective. The design of this study is qualitative research by gathering oral literature data on Raas Island. The data were collected through observation, video recording, tape recording, note-taking, and interviews. The results of the analysis showed that SLPR corresponds to the marginalization of women, as represented in riddles (bhag-tebhgan), proverbs (parebhasan), and folktales (careta rakyat). Women, through SLPR, are portrayed as weak creatures, sex objects, and sluts.